Decrease in the Photosynthetic Performance of Temperate Grassland Species Does Not Lead to a Decline in the Gross Primary Production of the Ecosystem - Digrado, Anthony; de la Motte, Louis G.; Bachy, Aurélie; Mozaffar, Ahsan; Schoon, Niels; Bussotti, Filippo; Amelynck, Crist; Dalcq, Anne-Catherine; Fauconnier, Marie-Laure; Aubinet, Marc; Heinesch, Bernard; du Jardin, Patrick; et al. (Frontiers in Plant Science, 2018)
Plants, under stressful conditions, can proceed to photosynthetic adjustments in order to acclimatize and alleviate the detrimental impacts on the photosynthetic apparatus. However, it is currently unclear how adjustment of photosynthetic processes under environmental constraints by plants influences CO2 gas exchange at the ecosystem-scale. Over a two-year period, photosynthetic performance of a temperate grassland ecosystem was characterized by conducting frequent chlorophyll fluorescence (ChlF) measurements on three primary grassland species (Lolium perenne L., Taraxacum sp., and Trifolium repens L.). Ecosystem photosynthetic performance was estimated from measurements performed on the three dominant grassland species weighed based on their relative abundance. In addition, monitoring CO2 fluxes was performed by eddy covariance. The highest decrease in photosynthetic performance was detected in summer, when environmental constraints were combined. Dicot species (Taraxacum sp. and T. repens) presented the strongest capacity to up-regulate PSI and exhibited the highest electron transport efficiency under stressful environmental conditions compared with L. perenne. The decline in ecosystem photosynthetic performance did not lead to a reduction in gross primary productivity, likely because increased light energy was available under these conditions. The carbon amounts fixed at light saturation were not influenced by alterations in photosynthetic processes, suggesting photosynthesis was not impaired. Decreased photosynthetic performance was associated with high respiration flux, but both were influenced by temperature. Our study revealed variation in photosynthetic performance of a grassland ecosystem responded to environmental constraints, but alterations in photosynthetic processes appeared to exhibit a negligible influence on ecosystem CO2 fluxes.